The Perspective of Applied Ecological Ethics on Cement Industry Development and Environmental Conservation in Relation to Christian Religious Education - Jawakory, Patricia Ina; Wijiati, Wahyu (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2025)
This study examines the perspective of applied ecological ethics on the development of cement factories and environmental conservation, as well as its relevance to Christian Religious Education (PAK). The research is motivated by increasing environmental degradation caused by industrial expansion, particularly in karst regions such as Kendeng, Central Java, which has generated ecological, social, and moral conflicts. A theological qualitative approach is employed, using hermeneutical analysis and literature studies to explore ecological ethical principles within the framework of Christian theology and their implications for industrial development issues. The findings indicated that industrial development must consider ethical responsibilities in managing natural resources sustainably, equitably, and without compromising environmental integrity. In this context, Christian Religious Education plays a crucial role in fostering ecological awareness, strengthening moral sensitivity, and cultivating a sense of responsibility toward the environment among learners and church communities. PAK also serves as a value-based educational platform that encourages concrete ecological action amid increasing industrial pressures. The study concludes that applied ecological ethics within the Christian perspective provides a moral foundation for society and educational institutions to engage in environmental preservation. By integrating ecological values into Christian Religious Education, development practices can be directed toward greater justice, sustainability, and responsible stewardship of the earth.